Challenges of viticulture adaptation to global change: tackling the issue from the roots. (8th December 2020) - Marín, D.; Armengol, J.; Carbonell‐Bejerano, P.; Escalona, J.M.; Gramaje, D.; Hernández‐Montes, E.; Intrigliolo, D.S.; Martínez‐Zapater, J.M.; Medrano, H.; Mirás‐Avalos, J.M.; Palomares‐Rius, J.E.; Romero‐Azorín, P.; et al.
Abstract: Viticulture is facing emerging challenges not only because of the effect of climate change on yield and composition of grapes, but also of a social demand for environmental‐friendly agricultural management. Adaptation to these challenges is essential to guarantee the sustainability of viticulture. The aim of this review is to present adaptation possibilities from the soil‐hidden, and often disregarded, part of the grapevine, the roots. The complexity of soil–root interactions makes necessary a comprehensive approach taking into account physiology, pathology and genetics, in order to outline strategies to improve viticulture adaptation to current and future threats. Rootstocks are the link between soil and scion in grafted crops, and they have played an essential role in viticulture since the introduction of phylloxera into Europe at the end of the 19th century. This review outlines current and future challenges that are threatening the sustainability of the wine sector and the relevant role that rootstocks can play to face these threats. We describe how rootstocks along with soil management can be exploited as an essential tool to deal with the effects of climate change and of emerging soil‐borne pests and pathogens. Moreover, we discuss the possibilities and limitations of diverse genetic strategies for rootstock breeding.